2013
DOI: 10.3389/fncel.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal citalopram exposure decreases serotonergic fiber density in the olfactory bulb of male but not female adult rats

Abstract: Manipulation of serotonin (5HT) during early development has been shown to induce long-lasting morphological changes within the raphe nuclear complex and serotonergic circuitry throughout the brain. Recent studies have demonstrated altered raphe-derived 5HT transporter (SERT) immunoreactive axonal expression in several cortical target sites after brief perinatal exposure to selective 5HT reuptake inhibitors such as citalopram (CTM). Since the serotonergic raphe nuclear complex projects to the olfactory bulb (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…1A,B). No brightly labeled somata were visible, confirming previous reports that 5-HT is most densely located in the GL but its origin is purely extrinsic (Takeuchi et al, 1982;McLean and Shipley, 1987;Zhang et al, 2013).…”
Section: Serotonergic Fibers Densely Innervate the Glomerular Layersupporting
confidence: 89%
See 1 more Smart Citation
“…1A,B). No brightly labeled somata were visible, confirming previous reports that 5-HT is most densely located in the GL but its origin is purely extrinsic (Takeuchi et al, 1982;McLean and Shipley, 1987;Zhang et al, 2013).…”
Section: Serotonergic Fibers Densely Innervate the Glomerular Layersupporting
confidence: 89%
“…It is unlikely that this labeling in the GCL came from unintended infection of other nuclei, such as the locus coeruleus, known to project to the GCL (McLean et al, 1989;Shipley and Ennis, 1996;Linster and Fontanini, 2014), as such nuclei are too far with our small injections to reach. The lack of attention so far given to the GCL innervation is likely due to the sparser serotonin labeling there, observed with antibodies against 5-HT or SERT alike (Takeuchi et al, 1982;McLean and Shipley, 1987;Zhang et al, 2013), in addition to not fully resolving different OB layers or distinct raphe divisions with previous wheatgerm agglutinin injections (McLean and Shipley, 1987). Similarly, it is possible that neuromodulatory effects in the GL that were previously observed through electrical stimulation of the DRN (Petzold et al, 2009) could be attributed to unintended recruitment of the MRN neurons, as they are located in close proximity to the DRN.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that observed deficits after early exposure to CTM seen only in males were reported in other studies after similar drug applications (20,45,46). For example, it has been shown that impaired social behavior and response to novelty are more obvious in CTM-exposed male compared with female rats (20).…”
Section: Discussionmentioning
confidence: 50%
“…As SRI exposed animals mature they demonstrate decreased serotonergic tone, possibly reflecting prolonged activation of inhibitory receptors (i.e., 5HT 1a ) (9). Together these findings suggest that altered 5HT auto-inhibitory feedback in the presence of high serotonergic tone (i.e., secondary to SRI exposure or genetically absent 5HT transporter (5HTT) protein) results in a constrained maturation and function of the 5HT system in ways that paradoxically link prenatal SRI exposure with an increased risk for affective disorders later in life (10,11). To date, there is a remarkable paucity of human studies of childhood outcomes following fetal modulation of 5HTT functions or exposure to high 5HT levels during fetal brain development.…”
mentioning
confidence: 86%